Language processing in social context - Dietrich, Rainer; Graumann, Carl F. (North-Holland Linguistic Series: Linguistic Variations, 1989)
The book presents an interdisciplinary analysis of social, cognitive, situational and contextual aspects of language and language processing by first and second language speakers. Linguists and psychologists formulate theoretical models and empirical analyses of the influence of such factors on various levels of language processing. These relate specifically to syntactic and semantic parsing, lexical selection, and text production. The issue of "hearer orientation'' in language use lies at the forefront of interest in this anthology and is tackled from such different fields as linguistics, te